Struktur Komunitas Teripang di Pantai Timur Surabaya - Winarni, Dwi (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
The objectives of this research were to obtain diversity, relative abundance, distribution, and habitat preference of sea cucumber species along east Surabaya coastal. Identification, data distribution, relative abundance and habitat preference of sea cucumbers were observed at 12 sites along Surabaya east coastal. Parameters to describe environment were water depth, brightness level of water, pH (water and substrate), salinity (water and substrate) and the texture of substrate. The texture of substrate was determined based on particles diameter of substrate (ASTM method). The research revealed that during September 2009 until October 2010, physical and chemical parameters of environment didnât change relatively, and the sea cucumber community in east Surabaya coastal composed of seven species, namely Phyllophorus dobsoni, Paracaudina australis, Cholochirus quadrangularis, Holothuria sanctori, Holothuria sp., H. forskali, and H. turriscelsa. Phyllophorus dobsoni was the most abundant species and could be found almost at all sampling sites while sandy substrate was the preferred habitat.Keywords: sea cucumber, distribution, habitat preference, east Surabaya coastal